Role of blood neutrophil to lymphocyte ratio and serum total IgE in diagnosis of asthma-COPD overlap among patients with COPD - Islam, Md Monimul; Hossain, Md Ali; Bennoor, Kazi Saifuddin; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2020)
Background: Some clinical and spirometric features are common to both COPD and asthma-COPD overlap (ACO), causing difficulties in distinguishing these airway diseases from each other. Since, both of them are characterized by airway inflammation, any inflammatory biomarker as blood neutrophil to lymphocyte ratio and serum total IgE can be used for this purpose. Objectives: To assess the role of blood neutrophil to lymphocyte ratio and serum total IgE in the diagnosis of ACO among patients with COPD. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Dhaka from March 2019 to February 2020. For this, 63 male stable patients (age 40 to 80 years) of COPD were enrolled and 51 of them were finally selected according to exclusion criteria. Then these 51 COPD patients were divided into ACO and COPD-alone groups, based on criteria from the joint document by the Global Initiative for Asthma (GINA) and the Global Initiative for Chronic Obstructive Lung Disease (GOLD). Blood neutrophil to lymphocyte ratio (NLR) and serum total IgE of all patients were measured by standard lab procedure. For statistical analysis, Chi-Square test, Fisher exact test, Shapiro Wilk test, Mann-Whitney U test and receiver operating characteristic (ROC) curve analysis were done, as applicable. Results: Among the 51 COPD patients, 26 patients were diagnosed with ACO and 25 patients were with COPD-alone. Here, NLR was significantly lower (median 2.09 vs 3.43, respectively; p<0.001) in ACO patients than that of COPD-alone. In addition, NLR showed ‘very good’ (area under ROC curve 0.815) diagnostic accuracy. Conclusion: The present study reveals that, blood neutrophil to lymphocyte ratio, but not serum total IgE can play substantial role in diagnosis of ACO among the patients with COPD J Bangladesh Soc Physiol. 2020, December; 15(2): 54-60